(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Despite major improvements in outcome over the past decades, acute myeloid leukemia (AML) remains a life-threatening malignancy, with current survival rates of ∼ 70%. In this review we discuss different management, diagnosis and treatment in AML patients. The particular relevance of new diagnostic and prognostic molecular markers in AML is presented. The general management of AML as well as new therapeutic approaches are discussed.